Analysis of Λb→Λμ+μ- Decay in Scalar Leptoquark Model - Shuai-Wei Wang; Ya-Dong Yang (Advances in High Energy Physics)
We analyze the baryonic semilepton decay Λb→Λμ+μ- in the scalar leptoquark models with X(3,2,7/6) and X(3,2,1/6) states, respectively. We also discuss the effects of these two NP models on some physical observables. For some measured observables, like the differential decay width, the longitudinal polarization of the dilepton system, the lepton-side forward-backward asymmetry, and the baryon-side forward-backward asymmetry, we find that the prediction values of SM are consistent with the current data in most q2 ranges, where the prediction values of these two NP models can also keep consistent with the current data with 1σ. However, in some q2 ranges, the prediction values of SM are difficult to meet the current data, but the contributions of these two NP models can meet them or keep close to them. For the double-lepton polarization asymmetries, PLT, PTL, PNN, and PTT are sensitive to the scalar leptoquark model X(3,2,7/6) but not to X(3,2,1/6). However, PLN, PNL, PTN, and PNT are not sensitive to these two NP models.